HUBUNGAN PENGGUNAAN MEDIA SOSIAL DENGAN PERILAKU KONSUMSI MAKANAN BERISIKO DIABETES MELITUS PADA MAHASISWA ILMU KESEHATAN MASYARAKAT UNIVERSITAS NEGERI MANADO - Carmenita Jennifer, Mamosey; Telew, Agusteivie; Alva Supit (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Social media has become an integral part of the lives of today's college students. Platforms such as Instagram, TikTok and YouTube not only influence lifestyles in general, but also play a role in shaping food preferences and food consumption behaviors. Content that promotes certain foods, both healthy and unhealthy, can influence a person's food choices. The approach taken in this study is a quantitative approach with a cross-sectional research design. The sample used in this study were 68 final year students of the Public Health Science study program at Universitas Negeri Manado. The data collection technique used a questionnaire distributed through Google Form. Based on the results of the study, it was found that there is a relationship between the use of social media and risky food consumption behavior of developing diabetes mellitus in students of Public Health Sciences, Universitas Negeri Manado (p-value = 0.001).